Lesión bilateral de ligamento cruzado craneal y neuropatía periférica en un canino Golden Retriever con hipotiroidismo: Reporte de caso - Moreno, Giovanni (2024)
The case of a 6 -year -old female Golden Retriever is presented. She was limping in the left posterior limb. A 4/4 grade lameness, pain by palpating the knee, and a negative drawer test, but positive tibial compression was identified. No proprioceptive deficit or signs compatible with lesions joints in X-rays images were found. There was no response to treatment with Meloxicam and Tramadol and because a suspicion of partial rupture of the cranial cruciate ligament, the transposition of tibial tuberosity (TTT) procedure was chosen. The patient returned with lameness in the right hind limb right nine months later and after ruling out other causes of limp, the TTT was successfully performed in the affected limb. However, 18 months later he developed signs of peripheral neuropathy. Metabolic, infectious and hormonal profile analyses revealed increased serum alkaline phosphatase, decreased thyroxine (free T4) and thyroid-stimulating hormone (TSH) values within normal ranges according to the reference laboratory. Based on the patient's history and laboratory findings, the diagnosis was hypothyroidism, and the decision was made to supplement the patient with sodium levothyroxine. Remission of the nervous symptoms was observed 45 days after treatment.